Archaeological shell middens in the uruguayan coast: review and perspectives - Beovide, Laura; Martínez, Sergio (Revista Chilena de Antropología, 2015)
Shell middens were only recently identified in the Uruguayan coast. In this paper, coastal and littoral shell middens are reviewed considering the prevailing theoretical and methodological paradigms in Uruguayan Archaeology. Also, there are introduced new approaches and perspectives - in the study of shell middens of the Río de la Plata left margin.